Structural colors and physical properties of elytra in the jewel beetle,Chrysochroa fulgidissima, using surface analytical techniques - Lee, Jihye; Terlier, Tanguy; Jang, Yun Jung; Lee, Kang-Bong; Lee, Yeonhee (WILEY, 2020)
Structural coloration frequently originates from the interaction of light with multilayers of thin films in living organisms. One example where structural colors are created by multilayers is the jewel beetle,Chrysochroa fulgidissima, which has highly iridescent green elytra with longitudinal red stripes. We examine the structure, chemical information, and physical properties of the epicuticle of the jewel beetle by using atomic force microscopy (AFM), scanning electron microscopy (SEM), transmission electron microscopy (TEM), nanoindentation, and time-of-flight secondary ion mass spectrometry (ToF-SIMS). AFM and SEM were used to analyze the surface structures of the green elytra and red stripes of the jewel beetle's wing. SEM and TEM images obtained from the cross-sectioned cuticle samples of green and red areas indicated that the color arises from interference reflectors and reflectors consist of successive repeating layers of different electronic densities. Nanoindentation results showed that the green area of the elytron possesses a higher hardness and reduced modulus compared with the red area. To analyze the surface of the elytra and to compare multilayers of the green area with those of the red area, mass spectra and depth profiles were acquired by ToF-SIMS with C(60)and Ar cluster ion beams. The epicuticle consists of several layers with alternating high and low abundances of inorganic and organic fragment ions, with approximately 16 layers in the green and 12 layers in the red area. Therefore, ToF-SIMS combined with other analytical techniques indicate that multilayer reflection is a major mechanism of the jewel beetle's iridescence causing structural coloration.
Keywords: ION MASS-SPECTROMETRY; POLARIZED IRIDESCENCE; ORIGIN; SCALES